2009
DOI: 10.1111/j.1365-2052.2009.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the ovine β3‐adrenergic receptor gene (ADRB3) and its association with wool mean staple strength and yield

Abstract: We investigated the possibility that variation in ovine ADRB3 is associated with various wool traits, in particular mean staple strength (MSS). Polymerase chain reaction-single strand conformational polymorphism analysis of part of the ADRB3 intron was used to genotype 695 Merino lambs born on three farms in the South Island of New Zealand and which were shorn as 2-tooths. For each fleece, MSS, mean fibre diameter, mean staple length and yield were measured. The results from mixed-effects models and half-sib a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The association analyses were based on the methods described by Byun et al (2010), Forrest et al (2009), Lin et al (2009), and Hickford et al (2010). After analyzing the associations between MUC1 genotypes and milk traits, the additive and co-dominance effects of the significant MUC1 genotypes were tested.…”
Section: Discussionmentioning
confidence: 99%
“…The association analyses were based on the methods described by Byun et al (2010), Forrest et al (2009), Lin et al (2009), and Hickford et al (2010). After analyzing the associations between MUC1 genotypes and milk traits, the additive and co-dominance effects of the significant MUC1 genotypes were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Wool production and quality traits are polygenic and several of genes have been identified to be associated with wool production and quality trait. For example, it has been shown that the Desmoglein 4 ( DSG4 ) gene is associated with wool length and curvature [ 1 ], while the Beta-3 adrenergic receptor ( ADRB3 ) gene is associated with wool mean staple strength and yield [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of QTL mapping using linkage analysis (LA) and/or linkage disequilibrium (LD), based on panels of low to moderate-density markers, have been well documented [2] , [3] . Only a few major genes, e.g., the KRTAP6 gene (keratin-associated protein 6) [4] , the PROP1 gene (PROP paired-like homeobox 1) [5] and ADRB3 (beta3-adrenergic receptor) [6] , have been associated with wool traits using QTL linkage analyses or candidate gene studies.…”
Section: Introductionmentioning
confidence: 99%